0112 Lucid Dreaming Associated with Positive Waking Mood. (27th May 2020) - Carr, M; Stocks, A; Mallett, R; Konkoly, K; Freegard, M; Hicks, A; Crawford, M; Pigeon, W; Schredl, M; Bradshaw, C
Abstract: Introduction: Lucid dreaming (being aware that one is dreaming) is typically a positive experience that may enhance positive mood even after waking. There is concern, however, that lucid dreaming may interfere with sleep quality. In the current experiment, participants practiced common lucid dream induction techniques over the course of a week, and kept a daily sleep and dream diary. The study objective was to assess relationships between dream lucidity and subjective sleep quality, dream emotional content, and subsequent waking mood. Methods: There were 32 participants aged 19–33 in this open label, single arm study (mean=22.63±3.48; 6 males, 24 females). All participants completed a sleep and dream diary for 7 days that included scaled items (1–7 scale) concerning subjective sleep quality, negative and positive emotional intensity of a dream (if recalled). Participants also completed a 19-item lucidity questionnaire, and the Positive and Negative Affect Schedule. Average scores for the week were computed for all measures and Pearson's correlations conducted between lucidity and all other measures. Participants with no dream recall (n=5) were excluded. Within-subjects analyses were undertaken by selecting each participant's highest and lowest lucidity night (n=22; 5 participants with only minimum lucidity excluded). Results: Positive correlations were found between lucidity and dream positive emotion (r=.490, n=27, p=.009) and positive waking mood (r=.638, n=27, p< .001); there were no other significant correlations (all p>.1). Higher lucidity was associated with more positive dream content ( t (21)= -3.214, p =.004) and positive waking mood ( t (25)=-4.568, p <.001); no other significant differences were observed. Conclusion: These data indicate that lucidity is associated with positive dreams and waking mood, with no detriment to self-reported sleep quality. The findings provide preliminary support of lucid dreaming as an intervention to improve wellbeing and mood in the short term. Support: N/A